Pengukuran ketepatan shooting anggota ekstrakurikuler sepak bola pada sekolah menengah pertama di Bengkulu Selatan - Andro Wibowo Aji (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
The purpose of this study was to determine the level of shooting accuracy skills of participants in extracurricular activities 4 football at SMP N 11 Bengkulu Selatan. The sample from this study amounted to 15 participants whose data collection method was by kicking the ball five times into the goal with a target in the form of numbers, which later on all numbers will be added up and categorized as very good, good, moderate, less, very less. Based on the analysis data, it shows that the accuracy of shooting carried out by the participants in the extracurricular activities of SMP N 11 Bengkulu Selatan is in the medium category. The shooting accuracy skills of the participants in the extracurricular activities of SMP N 11 Bengkulu Selatan are moderate because the participants are dominated by new participants or grade 7 students, and they have never practiced with this training method before.